Effect of arbuscular mycorrhizal on growth and yield performance of aerobic rice - a review / Tusnar Tusman - Tusman, Tusnar (Faculty of Plantation and Agrotechnology, 2016)
Arbuscular mycorrhizae fungi (AMF) are the mainly common in crops that grow in soil mineral, and very important for growing plants in nutrient-deficient substrates such as soil and sand dunes surrounding the volcano. Arbuscular mycorrhizae (AM) fungi are the largest population in plant community with high diversity such as tropical rainforests and temperate grasslands where they have a lot of potential host plants and can take advantage of their ability to colonize a wide variety of hosts. Also mycorrhizae plays an important role in the field of sustainable development agriculture and has been help of symbiosis associations with plant roots. There are several types of arbuscular mycorrhizal (AM) and many types of arbuscular mycorrhizal well recognized to colonize more than a few vegetables, fruits, grains, cereal and industrial crops in Malaysia such as Rice, Oil palm, Rubber and Cocoa. This paper highlighted the arbuscular mycorrhizae fungus (AMF) symbiosis with aerobic rice has excellent impression. Function mycorrhizae increased uptake of nutrients, the performance on growth and yield of arbusuc1ar mycorrhizal symbiosis with aerobic rice and perform as a bio-protection and bio control against pathogens. In order to further enhance the benefits of arbuscular mycorrhiza, it requires proper application fertilizers that need for plants, especially phosphorus fertilizer and low tillage management practices.